The Sun Maid: A Story of Fort Dearborn - Raymond, Evelyn, 1843-1910 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Sun Maid: A Story of Fort Dearborn" by Evelyn Raymond is a historical novel written in the late 19th century. The narrative follows a young orphan girl, Kitty Briscoe, also known as the Sun Maid, who is taken into the care of an Indian chief, Black Partridge, against the backdrop of the impending conflict between Native Americans and white settlers near Fort Dearborn. The story delves into themes of identity, belonging, and cultural intersections, particularly through the experiences of Kitty and those around her. The opening of "The Sun Maid" introduces us to the troubled heart of Black Partridge as he walks homeward, filled with a sense of foreboding about his people's future and the dishonesty he perceives in the white settlers. The narrative swiftly moves to the innocent Kitty Briscoe, who has wandered away from the Fort, and her lively spirit brings a tentative warmth to the somber mood. Black Partridge encounters her as she sleeps on the path, leading to her being brought into the Indian village, highlighting the blending of their fates. The initial chapters set the stage for Kitty's transformative journey amidst cultural clashes, the reverberations of loss, and the emergence of new relationships, as she becomes entwined with the destinies of those in her new home. (This is an automatically generated summary.)
Release date is 2010-06-16
E-text prepared by D Alexander and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Chicago (Ill.) -- History -- To 1875 -- Fiction; Indian captivities -- Illinois -- Fiction; Fort Dearborn (Ill.) -- Fiction